Comparison of 30 Day Stroke and Death in Hybrid Intervention and Open Surgical Reconstruction for the Treatment of Tandem Carotid Bifurcation and Supra-aortic Trunk Disease. (January 2021) - Wang, Linda J.; Nixon, Thomas P.; Crofts, Sarah C.; Latz, Christopher A.; Goudreau, Bernadette J.; Conrad, Mark F.; Eagleton, Matthew J.; Clouse, W. Darrin
Abstract : Objective: The optimal approach for the treatment of tandem carotid bifurcation and supra-aortic trunk (SAT) disease remains controversial. The hybrid technique of carotid endarterectomy (CEA) with ipsilateral proximal endovascular intervention (IPE) has provided an attractive alternative to CEA with open SAT reconstruction (SATr). However, no studies have compared cohorts treated by these two approaches. Methods: Using the National Surgical Quality Improvement Program (2005–2017), patients who underwent CEA + IPE and CEA + SATr were identified. Non-occlusive indications were excluded. Primary outcomes included 30 day stroke, death, and their composite (stroke and/or death [SD]). Univariable and logistic regression analyses were performed. Results: In total, 372 patients were identified: 319 CEA + SATr and 53 CEA + IPE. SATr included 19 (5.9%) aorta to carotid bypasses, 22 (6.9%) carotid subclavian transpositions, 96 (30.1%) carotid carotid bypasses, 179 (56.1%) carotid subclavian bypasses, and three (0.9%) SAT endarterectomies. The mean age was 69 ± 10 years. The majority were men (53%), white (85%), and had a history of hypertension (84%). There were no demographic differences between the operative cohorts except that those having CEA + SATr were more likely to have hypertension (86% vs. 74%; p = .031). CEA + SATr had longer operative times and longer hospital length of stay. There were no differences in outcomes between the cohorts: stroke (CEA + SATr 4.1% vs. CEA + IPE 3.8%; p = .92), death (1.6% vs. 0%; p = .36), or SD (5.3% vs. 3.8%; p = .63). After risk adjustment, predictors of SD included symptomatic status (odds ratio [OR] 3.9, 95% confidence interval [CI] 1.1–13.5; p = .034), congestive heart failure (OR 16.5, 95% CI 2.0–136; p = .011), and return to the operating room (OR 8.5, 95% CI 2.3–30.8; p = .001). Operative method was not predictive ( p = .63). Conclusion: Outcomes following CEA + SATr and CEA + IPE are similar. Although proposed as a safer, less invasive alternative, the hybrid approach did not reduce the risk of operative stroke or death relative to open reconstruction for the treatment of occlusive, tandem carotid/SAT disease. Based upon lesion and patient factors, both may be considered management options in select patients.